До питання управління якістю надання освітніх послуг в закладах вищої освіти - Бардась А. В.; Замковий М. Ю. (НТУ "ДП", 2024)
Результати. У статті розкрито механізми забезпечення якості вищої освіти, продемонстровано їхню ефективність та здійснено порівняльний аналіз досвіду окремих закладів вищої освіти як України, так і деяких зарубіжних країн. Розкрито сутність соціологічних опитувань та продемонстровано їхнє значення для забезпечення якості вищої освіти. Results. The article reveals the mechanisms for ensuring the quality of higher education, demonstrates their effectiveness, and provides a comparative analysis of the experience of specific higher education institutions in both Ukraine and some foreign countries. It explains the essence of sociological surveys and demonstrates their importance in ensuring the quality of higher education.
On the issue of quality management in the provision of educational services in higher education institutions
Keywords: управління; менеджмент якості; система управління якістю; загальне управління якістю; цикл Демінга; бізнес-процес; організація; заклади вищої освіти; освітній процес; забезпечення якості; опитування; моніторинг; management; quality management; quality management system; total quality management; Deming Cycle; business process; organization; higher education institutions; educational process; quality assurance; surveys; monitoring